Enhancing Aluminum Alloy Properties Through Low Pressure Forging: A Comprehensive Study on Heat Treatments - Silvia Cecchel; Giovanna Cornacchia (Metals, 2025)
The weight reduction is a key objective in modern engineering, particularly in the automotive industry, to enhance vehicle performance and reduce the carbon footprint. In this context aluminum alloys are widely used in structural automotive applications, often through forging processes that enhance mechanical properties compared to the results for casting. However, the high cost of forging can limit its economic feasibility. Low pressure forging (LPF) combines the benefits of casting and forging, employing controlled pressure to fill the mold cavity and improve metal purity. This study investigates the effectiveness of the LPF process in optimizing the mechanical properties of AlSi7Mg aluminum alloy by evaluating the influence of three different magnesium content levels. The specimens underwent T6 heat treatment (solubilization treatment followed by artificial aging), with varying aging times and temperatures. Microstructural analysis and tensile tests were conducted to determine the optimal conditions for achieving superior mechanical strength, contributing to the design of lightweight, high-performance components for advanced automotive applications. The most promising properties were achieved with a T6 treatment consisting of solubilization at 540 °C for 6 h followed by aging at 180 °C for 4 h, resulting in mechanical properties of σy 280 MPa, σm 317 MPa, and A% 3.5%.